Strategi Manajemen Kelas Untuk Meningkatkan Kualitas Pembelajaran Abad 21 Di MI Muslimat NU Demak - Laili, Zumala; Yuni Ratnasari; Wawan Shokib Rondli (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
21st-century learning demands a classroom environment that fosters creativity, collaboration, communication, and critical thinking. Therefore, teachers need to implement classroom management strategies that are more adaptive and responsive to students' needs. This study aims to describe effective classroom management strategies for improving the quality of learning in MI Muslimat NU Demak, focusing on managing the physical environment, strengthening behavioral regulation through positive discipline, and utilizing learning-supporting technology. The study employed a descriptive qualitative method with data collection techniques including classroom observations, teacher interviews, and document analysis. The results indicate that flexible classroom management and the implementation of teacher-student interactions oriented toward emotional support can increase student engagement, independence, and behavioral regulation. The use of interactive evaluation media also strengthens learning motivation and creates a participatory classroom climate. These findings confirm that the integration of classroom management strategies and technological innovation can significantly improve the quality of learning in elementary schools. This study provides practical implications for teachers in designing effective, adaptive classrooms that meet the demands of 21st-century competencies.